Usability Evaluation of Tokopedia Application Version 3.242 Using System Usability Scale (SUS) Method - Manurung, Romarta Yemima; Dwi Krisbiantoro; Dias Ayu Budi Utami (Politeknik Ganesha Medan, 2024)
Indonesia is currently experiencing rapid growth in the e-commerce sector. Its One of the existing e-commerce is the Tokopedia application, Users of this application reach more than 10 million users so that there are a lot of positive and negative reviews given by users. After manually analyzing there are still many negative reviews on the application, not only that, there are still other problems found such as expeditions that cannot be selected, then payment methods that cannot COD or pay on the spot, and sometimes force closes that come out by themselves suddenly. Therefore, researchers tried to conduct a study on Tokopedia application user satisfaction with the SUS method to measure the level of usability of the application. System Usability Scale (SUS) method to evaluate its usability aspect. The evaluation results showed that the app earned an SUS score of 55, with a percentile rank of about 30%, placing it at grade D. Although still above average, the slight difference with the standard SUS score (68) indicates a potential improvement. In interpretation based on nature (Adjective), the application is in the OK category, with the level of acceptance (Acceptable) is in the Marginal category. The Net Promoter Score (NPS) results show the Detractor category, indicating a tendency to lack user enthusiasm for the application. Further evaluation is needed to identify aspects of usability that affect user perception and cause unsatisfactory NPS categories. Future research can design improvement strategies based on these findings, with the aim of increasing SUS scores and changing the NPS category to be more positive